Incidence and risk factors of venous thromboembolism following major abdominal surgery - Sitthichai Vachirasrisirikul (2018)
© 2016, Medical Association of Thailand. All rights reserved. Objective: Venous thromboembolism (VTE) has been recognized as a common surgical complication in Western populations more than in Asian populations. Guidelines recommend the routine use of pharmacological prophylaxis for high-risk general surgical patients to prevent VTE. However, the necessity of routine pharmacological prophylaxis for major abdominal surgery in Thai patients has not been clearly determined. The purpose of the study was to determine the incidence and risk factors of VTE in Thai patients undergoing major abdominal surgery. Material and Method: A prospective cohort study was conducted between January and September 2014 in our institution. One hundred sixty seven patients that underwent major abdominal operation were analyzed. For the diagnosis of deep vein thrombosis (DVT), a duplex Doppler ultrasonography was performed in all patients five to seven days following surgery and in patients suspected of DVT until four weeks after surgery. CT angiography of pulmonary vasculature was carried out in patients suspected of pulmonary thromboembolism (PE). All patients were divided into two groups, non-VTE and VTE groups. The Student t-test was used to compare all continuous variables between both groups. Fisher’s exact test was used to compare all categorical variables. The risk factors of VTE were identified by stepwise backward regression analysis and reported with risk ratio (RR) and 95% confidence interval (CI). A p-value of <0.05 was regarded as statistically significant. Results: VTE was diagnosed in six patients (an incidence of 3.6%, 95% CI 3.39-3.81), three patients for proximal DVT (1.8%) and three patients for PE (1.8%). All cases were symptomatic. By multivariable analysis, risk factors of VTE could not be identified. However, higher BMI and postoperative longer rest on bed trended to increase the risk for VTE. Conclusion: The incidence of VTE in Thai patients that underwent major abdominal operation is low (3.6%), even in the context of risk factors typically regarded as high risk. Further studies into this area are warranted, especially well-designed large studies to develop an accurate risk stratification model specific for the Asian population.